Analysis of Public Technology Collaborative Innovation Based on Private Technology: A Tripartite Evolutionary Game Approach - Yunjuan Liang; Xin Liang; Hua Wei (Complexity)
Public technology collaborative innovation serves as an essential driving force to implement the innovation-driven strategy as well as promote national and regional economic sustainable development. Moreover, strengthening the construction of public technology collaborative innovation system is likewise of great significance for strengthening the quality and technology level of enterprises, enhancing their independent innovation capability, and achieving strategic transformation. Particularly, collaborative innovation of public technology in accordance with mature private technology enables the efficient allocation of technological and economic resources. In practice, there are still issues including high innovation costs, insufficient motivation, and low efficiency of innovation. Existing research typically ignores the technical cooperation among multiple parties. An evolutionary game model of public technology collaborative innovation is established in this paper to examine the interaction mechanism among the government, enterprises, and technology owners. For the purpose of analyzing the dynamic evolution of public technology collaborative innovation behavior and its influencing factors, numerical simulation experiments were conducted with meaningful results: (1) Setting the cost and benefit allocation coefficient in a scientific manner contributes to system stability and promotes cooperation among game players. (2) Reasonable government subsidies and penalties can assist in the formation of an active technological innovation between the firm and the technology owner. (3) The pricing method of private technology transfer is a significant factor influencing the evolution process. Besides, the adoption of a technology pricing method on the basis of government interests is conducive to the formation of a stable tripartite win-win situation. The research on collaborative innovation of public technology is further expanded in this paper, offering a reference for the formulation of relevant policies aimed at promoting cooperation in public technology innovation.